Similar Functional Outcomes with Open and Minimally Invasive Gastrosoleus-Lengthening Techniques - Vinall, Phil (MD Conference Express, 2014)
When conservative management fails in the treatment of gastrocnemius or gastrosoleus contracture, surgical treatment is indicated. Standard techniques are open lengthening and percutaneous triple hemisections (Hoke). This article discusses a study comparing open and minimally invasive approaches to gastrosoleus lengthening